A Novel Experiment to Study the Roll Motion Characteristics of a Sailing Ship in a Landslide-Generated Wave in the Three Gorges Reservoir - Peiyin Yuan; Pingyi Wang; Yu Zhao (Advances in Civil Engineering)
Strong earthquakes, heavy rains, changes in reservoir water levels, and other external factors destabilize large rock masses causing them to fall into the water at high speed, thereby destroying the original ecological balance in the region. These occurrences cause fluctuations in water levels and form landslide-induced waves, which behave similar to tsunamis upon reaching the shore, a dam structure, or ships. The impact invariably threatens residents’ lives and properties in the upper and lower reaches of the reservoir area. In the current study, we conducted orthogonal experiments of landslide-induced impulse waves to assess their related hazards. To explore the effects of a landslide-generated wave on the roll characteristics of a ship, experimental model tests were performed using different speed vessels, landslide bodies, and navigation positions. Accordingly, a reasonable optimization strategy was proposed to provide technical support for ship navigation safety in regions of landslide-generated waves.